Capacity building through integration and transformational leadership - A case study - Sacha Michael Stocklin (Laureate Education Inc, 2011)
This article suggests that educational managers can have an influence through leadership by establishing certain moderators that integrate and shape the faculty into a solid team working towards a high performing organisation. The study looks at a case in China and draws suggestions that could be used in other similar settings. The conclusion is to make integration a crucial part of capacity building. DOI: 10.18870/hlrc.v1i1.28